2005
DOI: 10.1021/jm051118z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Synthesis of Triazole-Modified Resveratrol Analogues via Click Chemistry

Abstract: Resveratrol is a phytoalexin able to display an array of biological activities. We decided to replace the double bond with a triazole ring using the archetypical click reaction: the Huisgen [3 + 2] cycloaddition. Seventy-two triazole derivatives were synthesized via a parallel combinatorial approach. Preliminary data suggest that this procedure can lead to the synthesis of compounds that display some, but not all, of resveratrol's actions with increased potency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
123
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(127 citation statements)
references
References 26 publications
1
123
0
3
Order By: Relevance
“…Resveratrol possesses numerous therapeutic actions including cytotoxic activity, and therefore the rapid synthesis of these triazole containing resveratrol analogues has been utilised to generate an enormous chemical database for preliminary screening of analogues with an antitumoural potential. Some of the compounds screened were found to be more potent than resveratrol as cytotoxic/antiproliferative agents [137]. The quantitative structure-activity relationship (QSAR) demonstrated that the stereochemical diversity within the carbohydrate tails effectively interrogated the carbonic anhydrase (CA) active site topology, generating in some instances inhibitors with hCA IX selectivity, an important outcome in the quest for potential cancer therapy [138].…”
Section: Click Chemistry Of Triazole: New Horizonsmentioning
confidence: 99%
“…Resveratrol possesses numerous therapeutic actions including cytotoxic activity, and therefore the rapid synthesis of these triazole containing resveratrol analogues has been utilised to generate an enormous chemical database for preliminary screening of analogues with an antitumoural potential. Some of the compounds screened were found to be more potent than resveratrol as cytotoxic/antiproliferative agents [137]. The quantitative structure-activity relationship (QSAR) demonstrated that the stereochemical diversity within the carbohydrate tails effectively interrogated the carbonic anhydrase (CA) active site topology, generating in some instances inhibitors with hCA IX selectivity, an important outcome in the quest for potential cancer therapy [138].…”
Section: Click Chemistry Of Triazole: New Horizonsmentioning
confidence: 99%
“…29,30 Ethynyl-1,2,3-trimethoxybenzene 25d was synthesized by the Corey-Fuchs method (Scheme 1). 25,31 Next, the aromatic azides 27a-d were prepared by the reaction of aromatic amines 26a-d with t-BuONO/TMSN 3 using the protocol reported by Moses and co-workers 33 (Scheme 2 Compounds 17, 18 and 19 were more active against L. amazonenis than was pentamidine (IC 50 8.9 μM). Compound 17, an analogue of machilin G 3, was 8 times more active than pentamidine, while 18 and 19 were 2.5 and 1.2 times more active than pentamidine, respectively ( Table 2).…”
Section: Chemistrymentioning
confidence: 99%
“…Furthermore, click chemistry is a good strategy for synthesis of hybrids analogues of neolignans 1-3, what would permit to obtain preliminary information about structure-activity relationship (SAR) of the compounds 4-19 ( Figure 2). Although many studies have described the anticancer activity of triazole compounds with methoxy substitution patterns, 25 to date all possible position isomers of 1,4-diaryl-1,2,3-triazole derivatives of neolignans 1- 3 have not yet synthesized and tested against Leishmania sp. and T. Cruzi.…”
Section: Introductionmentioning
confidence: 99%
“…2 Glycosyl 1,2,3-triazole conjugates have appeared as interesting target molecules due to their potential to act as inhibitors for galectins 3 and RNA binding molecules. 4 In fact, 1,2,3-triazoles were reported as important heterocyclic pharmacophores for developing anti-viral 5 , anti-cancer 6 and antibiotic agents 7 . In addition, they are particularly promising because they can mimic the amide bond and they are not cleaved hydrolytically in contrast to amides present in glycopeptides.…”
Section: Introductionmentioning
confidence: 99%